A Bibliometric Analysis of Myopia Research in East Asia in the 21st Century: The Socio-Economic Status and Quantitative Analysis - Jihye Ahn MSc; Guenhei Kim PhD; Moonsung Choi PhD (SAGE Publishing, 2023)
The purpose of this study is to assess the quantity and quality of myopia related articles from 2001 to 2021 using bibliometric methods. The number of published articles and citations, the correlation analysis between gross domestic product (GDP) and annual publication number and citations was investigated. The proportion of myopia articles from East Asia accounted for 55.28% in 2021. The researchers from China published the most articles on myopia during 2001 to 2021, followed by Japan and South Korea. The annual number of articles and citations from China and South Korea showed an exponential increase with strong positive correlation with GDP. All 3 countries in East Asia are mainly researching refractive surgery, prevalence, and glaucoma, and research on children's myopia is particularly active in China, and in Japan. The researchers from East Asia published more than half of articles on myopia since 2019, in order of China, Japan, and South Korea. The annual number of articles and citations from China and South Korea showed an exponential increase with strong positive correlation with GDP whereas those from Japan did not. All 3 countries are mainly researching refractive surgery, and glaucoma, and research on children's myopia is particularly active in China, and in Japan.